Anteseden Kepuasan Dan Loyalitas Toko Src Dalam Melakukan E-B2b Pada Mitra SRC Melalui Aplikasi Ayo Src Toko Di Pulau Lombok - Nisrina Arieza Rahmadita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Grocery stores have the opportunity to utilize technology as a means to support their business processes. Apart from being used to market products, technology with several application features is used to help grocery stores run their business operations, such as shopping at their grocery stores online, such as what AYO SRC Toko does. The purpose of this study was to look at and analyze the effect of e-loyalty programs and e-service quality on e-loyalty through e-satisfaction on the e-B2B application of the AYO SRC Toko on Lombok Island. The type of research used is quantitative in the form of conclusive - descriptive with online questionnaire distribution methods. Questionnaires were given to SRC store operators on Lombok Island who had conducted e-B2B for the last six months. The sampling technique used in this study is non-probability sampling with the category of convenience sampling. The analysis was performed using the Partial Least Square (PLS) model. This research is expected that PT. SRCIS knows the factors that influence application user satisfaction and loyalty so that it can increase competitive advantage and strategic decision making. The findings of this study are that e-Service Quality has a significant positive effect on e-Satisfaction and e-Loyalty both direct and indirect, and conversely, the e-Loyalty Program has no effect on e-Satisfaction and e-Loyalty both direct and indirect. Managerial implications are aimed at AYO SRC Toko, e-B2B business people or those who want to set up similar e-B2B applications. Keywords: e-B2B; e-loyalty; e-loyalty program; e-satisfaction; e-service quality